Children with pulmonary atelectasis: clinical outcome and characterization of physical therapy - doi: 10.4025/actascihealthsci.v35i2.12302 (Acta Scientiarum. Health Sciences, 2013)
Pulmonary atelectasis is described as a state of a given region of lung parenchyma collapsed and non-aerated. This study aimed to describe the characteristics and clinical outcome of children with atelectasis, assisted by physical therapy service. This is a case report whose information was collected from records of children hospitalized at the University Hospital of Londrina/HU, in 2009. Seventeen patients with pulmonary atelectasis were treated, aged from 11 days to 9 years old. At initial assessment, 8 (47%) children had no signs of difficulty breathing. The most used techniques were the re-expansion techniques used in all patients (100%), the clearance techniques were performed in 16 (94%) children, and the deflated techniques were used for only one child. The mean number of physical therapy sessions performed for the resolution of atelectasis was 4, ranging from 2 to 9. All 17 cases of atelectasis treated by physical therapy had rapid resolution. Outcome of children treated was satisfactory at short term with low number of physical therapy attendances.